Enhanced performance of Bi2S3/TiO2 heterostructure composite films for solar cell applications - Saket Mathur; Victoria Bishop; Andrew Swindle; Wei Wei (Journal of Photochemistry and Photobiology)
Day to day energy production is shifting towards renewable energy sources as these sources become more economically viable while being less polluting to operate; solar energy has become one of the major sources of renewable energy. However, it currently relies on ultra-pure silicon ingots to produce commercial silicon photovoltaics, which prevents the cost of electricity being produced to compete with non-renewable energy production. A viable low-cost alternative for silicon based cells would be dye-sensitized solar cells (DSSCs), which are easier and cheaper to manufacture as they do not require expensive and delicate raw materials to make. Moreover, they could be made semi-flexible which allows for a greater variety of applications. A DSSC consists of three components, a photo-electrode, an electrolyte and a counter-electrode. When exposed to incident light, the complex photosensitizers in the photoelectrode release electrons which are transported to the external load, leaving the photoelectrode in an oxidized state. The electrons are collected by the counter electrode and used to reduce the electrolyte. This charged electrolyte then reduces the positively charged photoelectrode, allowing the process to begin again. To improve the efficiency of this process, we explore the use of bismuth sulfide (Bi2S3) and titanium oxide (TiO2) composite as photoelectrode material and investigate their impact on the efficiency of DSSC.